Peacemaker, and other stories: stories - Hine, David; Blackman, Malorie Richardson, Peter (Heinemann Educational Oxford, 1999)
The guided reading series texts are illustrated and carefully graded to interest pupils, as well as covering a wide range of the genres recommended by the "Framework for Teaching" document. They raise thought-provoking issues for discussion and fit 20 minute guided reading sessions.